Heritage without heirs? Tangible and religious cultural heritage of the Vlach minority in Europe in the context of an interdisciplinary research project (contribution to the subject) - Kocój, Ewa (Balcanica Posnaniensia. Acta et studia, 2015)
The article will analyze the principal problems concerning research on the cultural heritage of displaced communities in Europe from the perspective of the Vlach minority. Based on the field research conducted in several countries of Europe (e.g. Greece, Macedonia, Romania, Ukraine, Slovakia and Poland), I will present the main classification of the Vlach tangible heritage with special attention paid to the most important cultural monuments, including religious building developments (churches, icons, small religious architecture). I will portray the difficulties found in protecting this heritage and the role of cultural institutions in its preservation and exposition. It can be stated that the example of the Vlachs perfectly illustrates the complex processes related to cultures which were overwhelmingly subjugated by their neighbours and lost the fight. A neighbour, usually representing the culture of the majority, was stronger culturally, economically, politically and often militarily. The article focuses on the phenomena which classical anthropology used to inspect, claiming that its role is to protect what is fading into oblivion. Thus, the analysis of the Vlach culture presented herein refers to a much wider reflection, which is a synergy of ethnography, ethnology and cultural anthropology, and to the critical studies on heritage which are emerging in Poland.